Pain and Consolation from the Perspective of John - Aldave Medrano, María Estela (Concilium, 2025)
There are situations of suffering which appear in the fourth gospel which have distinct nuances from those that precede it. Jesus suffered because of the death of Lazarus (11:33-38) and when confronted with the perspective of his own death (12:27). Yet the dominant image is of self-control, and the reader knows that Jesus shares the vulnerability of the flesh with humanity (sarx: 12:27). John highlights the suffering of the disciples through illness, death, social religious and political conflict, and makes a proposal to integrate all of them into human existence. This proposal has its roots in the life and death on the cross of Jesus, when he calls upon the Spirit of life and consolation.